Public Perception of the Accountability of the Genteng Wetan Village Government's Financial Reports - Eka Puji Lestari; Mutmainnah (LP2M IAIN Palopo, 2025)
This study aims to understand in-depth how the community interprets the accountability of village government financial reports in Genteng Wetan Village, Genteng District, Banyuwangi Regency. This study used a qualitative approach with a descriptive design, where informants were selected using a purposive sampling technique. A total of 12 informants were involved, including the village head, village secretary, treasurer, BPD members, community leaders, and village residents. Data was collected through in-depth interviews, participatory observation, and document analysis such as village budget reports and village meeting minutes. The research results show that village governments have attempted to implement transparency through the publication of financial reports, but most residents do not understand the content and meaning of these reports due to limited financial literacy. Citizen participation in accountability forums is also low and tends to be symbolic. This finding confirms that the success of public accountability is not only determined by the availability of reports, but also by the public's ability to understand the information and engage in the oversight process. This study suggests that village governments increase the dissemination of financial reports in simple language, expand citizen participation, and optimize the use of the Village Financial System (Siskeudes) as a means of transparency.